(untitled) (European Journal of Pure and Applied Mathematics, 2022)
The main purpose of this paper is to introduce and study new topological properties called C-almost normality and L-almost normality. A space X is called a C-almost normal (resp. L-almost normal) space if there exist an almost normal space Y and a bijective function f : X → Y such that the restriction function f|A : A → f(A) is a homeomorphism for each compact (resp. Lindelöf) subspace A ⊆ X. We investigate these properties and present some examples to illustrate the relationships among them with other kinds of topological properties.